An evolutionary robust solar radiation prediction model based on WT-CEEMDAN and IASO-optimized outlier robust extreme learning machine. (15th September 2022) - Zhang, Chu; Hua, Lei; Ji, Chunlei; Shahzad Nazir, Muhammad; Peng, Tian
Highlights: A novel hybrid approach is proposed for solar radiation prediction. PWLCM mapping and Levy flight are used to improve ASO. The improved ASO algorithm is introduced to optimize the ORELM network. WT and CEEMDAN are used to decompose the original sequence into relative simple sub-modes. Ten benchmark models are used to verify the superiority of the proposed model. Abstract: As a kind of clean energy, solar energy occupies a pivotal position in energy applications. Accurate and reliable solar radiation prediction is critical to the application of solar energy. In particular, a novel solar radiation prediction based on wavelet transform (WT), complete ensemble empirical mode decomposition with adaptive noise (CEEMDAN), improved atom search optimization (IASO) and outlier-robust extreme learning machine (ORELM) is proposed for solar radiation prediction. First, WT is used to denoise the original solar radiation time series, and CEEMDAN method is used to decompose the denoised sequence into intrinsic mode function (IMF) components with different distributions according to the fluctuation scale. Then the IASO algorithm is used to optimize the weights and thresholds of the ORELM to improve the performance of the ORELM model. Levy flight is added to the ASO to enhance the local and global search capability while the chaos population initialization based on piecewise linear chaotic map (PWLCM) is taken to improve the randomness and ergodicity of the initial population within the feasible region. Finally, the comparison with other benchmark models verifies the robustness and accuracy of the proposed solar radiation prediction model.